The influence of service quality on sustainable competitive advantage in Kurdistan Iraq hotels: Perspective from hotel managers - Abdul-Aziz Ahmad M.; Jais J. (Conscientia Beam, 2024)
In today's ever-evolving and highly competitive market, hotels across the globe face numerous challenges. Among these, a key challenge is providing and consistently maintaining an excellent quality of service. As customer expectations rise, businesses in the hospitality industry are under pressure and must learn how to develop resilient strategies. These strategies are imperative if they wish to maintain a sustainable competitive advantage (SCA) amidst the intense competition they face daily. Interestingly, past studies often assumed the factors that predict competitive advantage, often disregarding the substantial impact of service quality (SQ). This error may incur significant costs. Therefore, to remain and become more competitive, logistic service providers (LSPs) should deeply understand the salient factors that contribute to building up their competitive advantage. They must also recognize the pivotal role of SQ and grasp its profound effect on SCA. The present research uniquely aims to assess the intricate relationship between SQ and SCA, particularly concerning hotel managers. Through this study, 152 sampled questionnaires were diligently obtained from hotel managers in the vibrant Kurdistan region of Iraq. These responses were thoroughly analyzed. Notably, the results demonstrated that all SQ dimensions, with the exception of assurance, were significant for ensuring the overall SCA of hotels. This groundbreaking study is the first of its kind to be conducted in this region. Ultimately, the valuable outcome of this study will guide and assist hotel managers in meticulously focusing on and enhancing their SQ levels, especially in the Kurdistan region. 2023 Conscientia Beam. All Rights Reserved.